Analizar el impacto de la adopción o convergencia por primera vez de la NICSP 17, propiedad planta y equipo en la entidad gubernamental -FINANDENA-, de acuerdo con los estados financieros de la vigencia fiscal 2012 (2013)
This research has been aimed at analyzing the impact of the adoption or convergence of International Accounting Standards IPSAS Public Sector No 17 - Property, Plant and Equipment, at the National Development Financial Institution-FINANDENA with balance sheet information at December 31/2012. To this end, I inquire about international standards, its definition, characteristics, applicability and finally as adopted by the Company, through a comparison of the current rules for handling COLGAAP Plant and Equipment Property, comparing with IPSAS-17.